Evaluation of Routine hematological parameter and Red Cell Distribution Width (RDW) in Myocardial Infarction patients admitted at Dhiraj Hospital - Mritunjay Kumar Mishra; DVSS Ramavataram; Tejas Shah; Swapan Goswami (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: - An increased systemic and local inflammation in vascular rupture plays a key role in thepathophysiology mechanism of acute coronary syndrome (ACS). Routine complete blood count (CBC) isone of the most common and conventional blood test that physicians test cycle.Objective: To study the level of routine hematological parameters and red cell distribution width inMyocardial Infarction.Methodology: - A cross sectional type of study carried out in the department of biochemistry, Smt. B.K.Shah Medical Institute & Research center, Sumandeep Vidyapeeth Vadodara Gujarat. A total 100 myocardialinfarction patients with age group of 25-70 of either gender were collected from Dhiraj General Hospital.Pathological parameter were analyzed by BACKMAN COULTER SYSMEX Kx-21N.Results: - In the age wise distribution of MI patients, we found more number in 58 to 68 age group. Themean levels of pathological parameter were observed with in reference range. In the observation of age wisepathological parameter we found that there increases mean levels of leucocyte count and the mean level ofRDW (18.50±1.80) is increased in 58-68 age group.Conclusion: - RDW is one of the predictive biomarkers for diagnosis of myocardial infarction with cardiacmarkers especially cardiac troponin I (cTn-I). Platelet levels can be monitored in MI patients in early phaseto find out the status of clot.